2014
DOI: 10.1016/j.ijsolstr.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of contact stiffness heterogeneities on friction-induced vibration

Abstract: International audienceIt is well-known that the occurrence of squeal depends on numerous phenomena still relatively unknown. Furthermore, squeal is affected by several factors on both the micro and macro scales. The present paper proposes some potential interactions between stiffness heterogeneities of the contact surface and the potential for triggering the squeal. Consequently, an analytical model has also been developed to highlight the impact of certain parameters on the squeal phenomenon. The contact surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…From the results in the above section, two macroscopic contact zones corresponding to the two different unstable frequencies are assumed (Figure 17). In order to study the influence of plateaus distribution on mode-coupling instability at 2100 Hz, as in [14], the macroscopic unstable contact zone is divided in a certain number of uniform patches (Figure 17a). Each patch is independent from each other.…”
Section: Mesoscopic Scalementioning
confidence: 99%
See 2 more Smart Citations
“…From the results in the above section, two macroscopic contact zones corresponding to the two different unstable frequencies are assumed (Figure 17). In order to study the influence of plateaus distribution on mode-coupling instability at 2100 Hz, as in [14], the macroscopic unstable contact zone is divided in a certain number of uniform patches (Figure 17a). Each patch is independent from each other.…”
Section: Mesoscopic Scalementioning
confidence: 99%
“…The height distribution of asperities reportedly affects the tangential contact stiffness and can lead to self-excited vibration. Magnier et al [14] proposed an analytical model with a contact interface including stiffness heterogeneities between pad and disc and demonstrated the influence of these kinds of heterogeneities on mode lock-in. They found that if the size of heterogeneities is large, the effect of contact localization is important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the phenomena at the origins of such noises are stick-slip [20]. The appearance of stick-slip instability is influenced by the combination of several tribological and dynamical processes and parameters [21,22], which in real systems are difficult to discern. One cause of instability is a falling characteristic of the friction coefficient with the relative velocity that may lead to negative damping, causing stick-slip oscillations [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…To have the most appropriate model to describe vibration induced by friction in braking systems, there are four mechanisms to consider: stick-slip, sprag-slip, variable dynamic friction coefficient, and mode-coupling of degrees of freedom (DOF). 811 For squeal noise, it is generally associated with geometric instability or mode-coupling instability. 12 Numerous research works have conducted many modeling proposal to investigate the friction-induced vibration in brake squeal, and we can classify these models into two categories: finite element method and minimal analytic model.…”
Section: Introductionmentioning
confidence: 99%